2006
DOI: 10.1039/b514103f
|View full text |Cite
|
Sign up to set email alerts
|

The spore photoproduct lyase repairs the 5S- and not the 5R-configured spore photoproduct DNA lesion

Abstract: The spore photoproduct lyase is a Fe-S/AdoMet DNA repair enzyme, which directly repairs spore lesions, induced by UV irradiation of spores, using an unknown radical mechanism. The air sensitive radical SAM enzyme was for the first time challenged with synthetically pure substrates. It was found that the enzyme recognizes a synthetic 5S-configured spore lesion without the central phosphodiester bond. The 5R-configured lesion is in contrast to current belief not a substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 27 publications
3
51
3
Order By: Relevance
“…PFL-AE, BioB, and LipA) in the radical AdoMet superfamily. Previously published reports indicated that SP lyase uses AdoMet as a cosubstrate (35,48); however, results from our laboratory demonstrate that SP lyase can repair SP using only catalytic amounts of AdoMet. The data in Table 1 illustrate this point.…”
Section: Overexpression and Purification Of Sp Lyasecontrasting
confidence: 56%
“…PFL-AE, BioB, and LipA) in the radical AdoMet superfamily. Previously published reports indicated that SP lyase uses AdoMet as a cosubstrate (35,48); however, results from our laboratory demonstrate that SP lyase can repair SP using only catalytic amounts of AdoMet. The data in Table 1 illustrate this point.…”
Section: Overexpression and Purification Of Sp Lyasecontrasting
confidence: 56%
“…Enzymatic activity with SPTpT can also be compared with that obtained with an interstrand synthetic SP dinucleoside. With the same enzyme preparations and comparable assay conditions as those used in this study, we reported a specific activity of about 0.004 mol/mol/min using the dinucleoside substrate (18). This 60-fold difference in repair activity demonstrates the importance of the phosphodiester bridge, probably because it limits the conformational freedom of the substrate dimer and suggests that the enzyme is not effective in repairing interstrand lesions.…”
Section: Discussionmentioning
confidence: 50%
“…This new substrate provides a convenient assay for further enzymatic studies. Combined with a previous study addressing the question of the stereoselectivity of the enzyme (18), this work provides new insights into the chemistry of SP lyase.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…[51][52][53] Indeed, a mechanism has been proposed and is supported by experiments such as mutation studies on SP lyase, but structural information such as crystal structures is still lacking. 54,55 …”
Section: The Spore Photoproductmentioning
confidence: 99%